Knowledge of human papillomavirus, cervical cancer, and anti-HPV vaccine among students from a university in Goiás, Brazil - Thairine Carrijo do Prado; Leonardo Luiz Borges; Vera Aparecida Saddi; Andrea Alves Ribeiro; Silvia Helena Rabelo dos Santos (DST, 2016)
Introduction: Cervical cancer affects women worldwide. The etiological pathogen is the Human Papillomavirus (HPV). Despite the high incidence, there are some prevention programs that include Pap smear test and the anti-HPV vaccine. Objective: The objective of this study was to evaluate the perception and knowledge of HPV infection, cervical cancer, and anti-HPV vaccine among biomedicine students from the Pontifícia Universidade Católica de Goiás (PUC Goiás). Methods: A questionnaire was administered with objective questions in a multiple-choice format. The mean score for each group of questions was classified as follows: satisfactory, if above 80%; reasonable, between 70 and 80%; and unsatisfactory, when less than 70%. The data was transferred to the R Core Team 2012. In order to develop the statistical analysis, the chi-square test (χ2) was applied, with a confidence interval of 95% and a significant value below 0.05. Results: From 268 participants, the scores concerning the HPV infection varied from 23,2 to 99,6%, with an average of 75,7%; with regard to cervical cancer, scores ranged from 25,9 to 98,1% with an average of 68,9%; and regarding the anti-HPV vaccine, scores ranged from 14,3 to 97,4%, with an average of 69,3%. Conclusion: The results showed that the general performance of the academics was insufficient. We highlight the need for new strategies on undergraduate teaching about HPV, its complications and prevention.